Consumption patterns and attitudinal insights on artificial sweeteners in Saudi Arabia - Aljehany, Buthaina M.; Abduljawad, Eman A.; Alatwi, Fadhah; Benajiba, Nada (Frontiers in Public Health, 2025)
IntroductionArtificial sweeteners (AS) are increasingly used as sugar substitutes in Saudi Arabia, yet no studies have examined the patterns and attitudes related to their consumption.AimTo investigate AS consumption behaviors and attitudes among Saudi adults.MethodsA cross-sectional study was conducted among 386 Saudi adults using a validated online questionnaire, which included the Artificial Sweeteners Attitudes Scale (AASS) to assess acceptance, risk perception, perceived benefits, trust in regulators, and motivation for natural alternatives. Descriptive statistics summarized consumption patterns, and chi-square tests, regression analyses, and a hurdle model were applied to identify predictors of AS use.ResultsAbout 42% of participants reported regular AS consumption, with 65% using AS primarily for weight management and 74.19% believing AS supports a healthy lifestyle. Education level was significantly associated with AS use (p = 0.001). While 61.40% expressed acceptance of AS, concerns about health (44.30%) and a preference for natural foods (66.84%) remained. Frequency of AS consumption was significantly associated with AASS subscales including acceptance, perceived benefits, health risk perception, and preference for natural alternatives. Female gender (OR 1.8, 95% CI 1.2–2.6) and higher education (OR 1.5, 95% CI 1.1–2.1) emerged as significant predictors.ConclusionThis study highlights a high prevalence of AS use among Saudi adults, largely motivated by weight management goals but tempered by health concerns and a preference for natural foods. These findings underscore the need for targeted educational and public health interventions to support informed dietary choices.